Of Reynaert the Fox : text and facing translation of the Middle Dutch beast epic Van den vos Reynaerde - Bouwman, A. Th; Besamusca, Bart; Hüning, Matthias; Vogl, Ulrike (Amsterdam University Press, 2009)
The first-ever bilingual Dutch and English edition of Van den vos Reynaerde, the celebrated medieval Dutch beast epic featuring a crafty fox.